2017
DOI: 10.1159/000478698
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Investigating Clinical Responses and Biological Pathways of Azelastine/Fluticasone in Nonallergic Vasomotor Rhinitis before and after Cold Dry Air Provocation

Abstract: Background: Nonallergic vasomotor rhinitis (NAVMR) has been considered a diagnosis by exclusion due to unknown mechanisms or lack of diagnostic biomarkers. Methods: To determine clinical responses and biological pathways in NAVMR subjects challenged to cold dry air (CDA) in an environmental exposure chamber (EEC) pre- and posttreatment with azelastine/fluticasone (AzeFlu), 30 NAVMR subjects, prescreened for CDA-induced symptoms (approx. 14°C, <15% relative humidity, ×1 h) were randomized to treatment with AzeF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Cough is also a common component of VMR. 77 ''Idiopathic rhinitis'' is sometimes used as an alternative term to VMR and usually excludes NARES. 78 However, the term is confusing as some studies have found high levels of eosinophils and mast cells in some patients categorized as having idiopathic rhinitis.…”
Section: Nonallergic Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…Cough is also a common component of VMR. 77 ''Idiopathic rhinitis'' is sometimes used as an alternative term to VMR and usually excludes NARES. 78 However, the term is confusing as some studies have found high levels of eosinophils and mast cells in some patients categorized as having idiopathic rhinitis.…”
Section: Nonallergic Rhinitismentioning
confidence: 99%
“…Nasal challenge for VMR, to determine nasal hyperresponsiveness (eg, using cold dry air or hypertonic saline in a challenge chamber), may be used in research to assess drug efficacy but is rarely used for clinical diagnosis. 77,80 More recently, optical rhinometry with intranasal capsaicin challenge has been demonstrated to assist in the diagnosis of a subset of patients with VMR and nonallergic irritant rhinitis. 81 While the pathophysiology of VMR is not fully understood, there is evidence that it involves a neurogenic pathway with an increase in neural efferent traffic to the nasal mucosa with an imbalance between parasympathetic and sympathetic nasal innervation.…”
Section: Nonallergic Rhinitismentioning
confidence: 99%
“…The trigeminal nerve has nociceptive Aδ and C fibers that are stimulated by physical and chemical ligands as well as products of allergic reactions 562 . Inflammatory mediators (e.g., bradykinin, histamine, acetylcholine, and capsaicin) are capable of activating sensory neurons in the trigeminal nerve, largely through TRP ion channels 563–566 . Through repeated depolarization, lasting changes develop in TRP channels as demonstrated for the TRP cation channel subfamily V member 1 (TRPV1) and subfamily A member 1 (TRPA1).…”
Section: Pathophysiology and Mechanismsmentioning
confidence: 99%
“…Depolarization of these nociceptive channels on sensory nerves leads to the release of neuropeptides including substance P, CGRP, and neurokinin‐A 564 . Substance P receptors are located on nasal epithelium, glands, and arterial and venous vessels, and sinusoidal vessels, which leads to glandular secretion, increased vessel permeability, edema, vasodilation, and further activation of inflammatory cells 562,566,567 .…”
Section: Pathophysiology and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation